Dekonstruksi Konsep Kesejahteraan: Analisis Komparatif Paradigma Ekonomi Konvensional dan Ekonomi Islam Berbasis Instrumentasi Maqasid Syariah Imam Asy-Syathibi - Kusnadi Kusnadi; Taufik Taufik (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2024)
The measurement of societal welfare currently faces a conceptual and epistemological crisis driven by the dominance of a conventional economic paradigm that is inherently materialistic, secular, and utilitarian. Conventional quantitative monetary indicators—such as GDP, alongside metrics from BPS and BKKBN—have proven blind to wealth distribution, neglectful of moral degradation, and prone to the Easterlin Paradox. This study aims to conduct an epistemological deconstruction of the conventional welfare concept and operationalize Imam Asy-Syathibi’s Maqasid Shariah framework to reformulate and re-map conventional material indicators (BPS and BKKBN) into a holistic welfare matrix. Employing a qualitative library research design, this study utilizes a descriptive-comparative and deconstructive approach analyzed through qualitative content analysis. The findings reveal that conventional physical-material indicators should not be discarded entirely; rather, they must be repositioned as instrumental means (dharuriyah-hajiyah) under the pillars of protecting life (Hifz an-Nafs) and wealth (Hifz al-Mal). Crucially, the validity of these material achievements is strictly governed by a moral filter system grounded in the protection of religion (Hifz ad-Din), intellect (Hifz al-'Aql), and lineage (Hifz an-Nasl). The implications of this study propose a strategic action plan advocating for the adoption of the Maqasid Shariah Welfare Index (MSWI) as a complementary national evaluation tool for policy-makers, as well as a comprehensive benchmark for evaluating empowerment outcomes in Islamic social finance institutions (ZISWAF).